Stabilization and controlled release of gaseous/volatile active compounds to improve safety and quality of fresh produce. (January 2020) - Chen, Mo; Chen, Xi; Ray, Soumi; Yam, Kit
Abstract: Background: Gaseous/volatile active compounds are effective tools for pre-harvest and postharvest management/preservation of fresh produce, e.g., 1-methylcyclopropene (1-MCP) and ethylene for regulating ripening, and chlorine dioxide (ClO2 ) and sulfur dioxide (SO2 ) for inhibiting microbial growth. Various approaches for their stabilization and controlled release have been developed to improve the safety and maintain the quality of fresh produce. Scope and approach: This paper reviews and categorizes the approaches to stabilize and control the release of selected active compounds, including 1-MCP, ClO2, ethylene, SO2, and essential oils. Knowledge and research gaps are also discussed. Examples of some commercially available systems are used to demonstrate how to stabilize and achieve controlled release for different applications and purposes. Key findings and conclusion: Various methods can be used to develop formulations/compositions in different forms to achieve stabilization and controlled release. Since moisture/water is often used to initiate the release, most methods focus on controlling water penetration into the formulation/composition. Among various forms of application, fumigation in storage rooms is the most commonly applied. There is also a growing interest to develop controlled release packaging systems. More efforts are needed to understand the physical and chemical interactions between the active compounds and the formulation/composition to predict the retention and release kinetics of the active compounds. Researchers should also be mindful of the regulatory limitations of these compounds to ensure the practicality of the research data. Highlights: Stabilization and controlled release are critical for gas/volatile application. Efforts are needed to study stability of active compounds in the stabilized system. Packaging systems for delivery of gas/volatile are of growing interest. Researchers should be mindful of the regulatory limitations.